Identification of Key Candidate Genes Involved in Aluminum Accumulation in the Sepals of Hydrangea macrophylla - Shuwen Luo; Ying Li; Yibing Wan; Youwei Fan; Chun Liu; Suxia Yuan (Horticulturae, 2024)
Hydrangea macrophylla (H. macrophylla), a species in the genus Hydrangea in the family Hydrangeaceae, is widely valued for its ornamental qualities in both domestic and international markets. Notably, H. macrophylla is known for its ability to accumulate aluminum (Al). Moreover, aluminum ions (Al3+) participate in sepal bluing. However, the underlying mechanisms of Al accumulation in the sepals remain unclear. In this study, we utilized transcriptome data from two cultivars to identify genes associated with Al accumulation. In total, 154 differentially expressed isoforms between the CK and Tr groups in the sepals of both cultivars were screened. Through gene enrichment analysis and similarity identification in the CDS (coding sequence) region, 43 differentially expressed genes were identified, including 30 upregulated and 13 downregulated genes, in the sepals of the Al treatment group. Further analysis revealed that seven of these upregulated genes are related to Al accumulation in sepals. Among the seven, the gene HmALS3.1 was identified as a potential key player in Al transport within the sepals of H. macrophylla. This study lays the groundwork for further exploration into the mechanisms by which HmALS3.1 regulates Al accumulation in H. macrophylla.